Presenting the Management Accounting Model in the Digital Era - Gholami, Abdolkarim; Khanmohamadi, Mohamad Hamed; Vakilifard , Hamidreza; Ranjbar , Mohamadhosein (Management Strategies and Engineering Sciences, 2025)
Digital technologies, including artificial intelligence and data analytics, have empowered organizations to make decisions with increased accuracy and speed. The objective of this study was to develop a management accounting model tailored to the demands of the digital era. This research is applied in nature and employed a qualitative methodology grounded in grounded theory. Data were collected through a combination of library research, reviews of specialized academic sources, and semi-structured interviews. Purposeful sampling was used to select 20 participants, including managers and shareholders from the stock exchange as well as financial management experts, during the year 2023. The interview data were coded using ATLAS.ti software. To ensure the validity of the findings, the data underwent qualitative analysis using three classification stages. The results were organized into five categories: causal, contextual (background), intervening, strategic, and consequential. The final model consists of six overarching categories and 16 core codes derived from 109 initial codes. Causal conditions included scientific and technological advancements, along with changes in business and managerial environments. Strategies identified in the model involved the development of education systems, infrastructure enhancement, and targeted financial reporting and policy-making. The consequences of implementing this model included improved decision-making efficiency, enhanced business growth, and increased economic productivity. Contextual conditions encompassed the broader economic and political landscape and the current state of accounting practices. Intervening conditions involved factors such as institutional negligence, cultural and societal influences, accessibility of resources, and environmental determinants. In the digital era, access to vast amounts of high-quality data has enabled more precise analysis. The proposed data-oriented management accounting model—leveraging data analytics tools and artificial intelligence—has significantly improved the precision of financial and strategic decision-making. This approach provides managers with more reliable and actionable insights, thereby enhancing organizational performance and supporting the achievement of long-term objectives.